A mixed-methods evaluation of community-based healthy kitchens as social enterprises for refugee women - Sahyoun, Nadine R.; Jamaluddine, Zeina; Choufani, Jowel; Mesmar, Sandra; Reese-Masterson, Amelia; Ghattas, Hala (Springer, 2019)
Background The aim of this study is to investigate the potential impact of a community-based intervention - the Healthy Kitchens, Healthy Children (HKHC) intervention - on participating women’s household’s economics and food security status, decision making, mental health and social support. Methods We established two healthy kitchens in existing community-based organizations in Palestinian camps in Lebanon. These were set up as small business enterprises, using participatory approaches to develop recipes and train women in food preparation, food safety and entrepreneurship. We used a mixed-methods approach to assess the impact of participating in the program on women’s economic, food security, decision making, social and mental health outcomes. A questionnaire was administered to women at baseline and at an 8-month endpoint. The end line survey was complemented by a set of embedded open-ended questions.